IMPLEMENTATION OF THE MERDEKA BELAJAR CURRICULUM THROUGH THE APPLICATION OF PROJECT-BASED LEARNING MODELS TO IMPROVE STUDENT LEARNING OUTCOMES IN MATHEMATICS LEARNING: IMPLEMENTASI KURIKULUM MERDEKA BELAJAR MELALUI PENERAPAN MODEL PEMBELAJARAN BERBASIS PROJECT UNTUK MENINGKATKAN HASIL BELAJAR SISWA DALAM PEMBELAJARAN MATEMATIKA - Baharullah; Sri Satriani; Fathrul Arriah; Ashar Hidayah (Department of Mathematics Education Faculty of Tarbiyah and Teacher Training Universitas Islam Negeri Alauddin Makassar, 2022)
The merdeka curriculum is a form of evaluation of the previous curriculum, namely the 2013 curriculum. In an independent curriculum, students are no longer forced to study subjects that are not their main interest. Therefore, a learning model is needed to support this independent curriculum's implementation. One suitable learning model to implement the curriculum is a project-based learning model. This study aims to improve student learning outcomes in mathematics learning through the Project Based Learning learning model. This type of research is classroom action research with data collection carried out through observations, and tests. The research subject is class XII in statistics subject totaling 26 students. The data analysis technique used qualitative and quantitative and was carried out for 2 cycles. The results showed that the application of the project-based learning model could improve student learning outcomes in learning mathematics. This can be seen from the average score of learning outcomes in the cognitive domain in the first cycle of 57.12% increased to 82.88% in the second cycle, the average score of learning outcomes in the psychomotor domain in the first cycle of 53.65% increased to 84.61%, and the average score of learning outcomes in the affective domain in the first cycle of 72.5% increased to 83.85%. This shows that the application of the project-based learning model can improve student learning outcomes.